New insights into lake responses to rapid climate change: the Younger Dryas in Lake Gościąż, central Poland. (16th December 2020) - Müller, Daniela; Tjallingii, Rik; Płóciennik, Mateusz; Luoto, Tomi P.; Kotrys, Bartosz; Plessen, Birgit; Ramisch, Arne; Schwab, Markus J.; Błaszkiewicz, Mirosław; Słowiński, Michał; Brauer, Achim
Abstract : The sediment profile from Lake Gościąż in central Poland comprises a continuous, seasonally resolved and exceptionally well‐preserved archive of the Younger Dryas (YD) climate variation. This provides a unique opportunity for detailed investigation of lake system responses during periods of rapid climate cooling (YD onset) and warming (YD termination). The new varve record of Lake Gościąż presented here spans 1662 years from the late Allerød (AL) to the early Preboreal (PB). Microscopic varve counting provides an independent chronology with a YD duration of 1149+14/–22 years, which confirms previous results of 1140±40 years. We link stable oxygen isotopes and chironomid‐based air temperature reconstructions with the response of various geochemical and varve microfacies proxies especially focusing on the onset and termination of the YD. Cooling at the YD onset lasted ~180 years, which is about a century longer than the terminal warming that was completed in ~70 years. During the AL/YD transition, environmental proxy data lagged the onset of cooling by ~90 years and revealed an increase of lake productivity and internal lake re‐suspension as well as slightly higher detrital sediment input. In contrast, rapid warming and environmental changes during the YD/PB transition occurred simultaneously. However, initial changes such as declining diatom deposition and detrital input occurred already a few centuries before the rapid warming at the YD/PB transition. These environmental changes likely reflect a gradual increase in summer air temperatures already during the YD. Our data indicate complex and differing environmental responses to the major climate changes related to the YD, which involve different proxy sensitivities and threshold processes.